Pengaruh Problem Based Learning Berbasis Media Puzzle Quiz Terhadap Hasil Belajar Siswa Materi Puasa Ramadhan - Francisca; Ani Nur Aeni; Dadan Nugraha (Elementary Teacher Education Program, Majalengka University, 2024)
The research was conducted because of the problem of low student learning outcomes in learning Islamic Religious Education in schools, especially elementary schools. One solution is to use interesting learning models and media, such as a problem based learning model based on puzzle quiz media. The aim of this research is to find out whether there is an influence and difference in improving student learning outcomes using the problem based learning model based on puzzle quiz media on the material of the month of Ramadan. The research method is a non-equivalent control group design quasi-experimental method with a sample of 30 students from the experimental group and the control group. The research was carried out in two schools, namely SDN Karangbaru as the experimental group and SDN Linggajaya as the control group. The results of research in the cognitive domain carried out using an independent t test showed that H1 was accepted, namely that there was an influence of the problem based learning model based on puzzle quiz media on Ramadan fasting material with a moderate influence test category based on the effect size test. Meanwhile, in the affective domain, the difference in the average attitude observation score of the experimental class at the first meeting and the second meeting was the average, with the results showing the difference in the average of the experimental and control classes. Meanwhile, in the cognitive domain, there is a difference in the increase in learning outcomes as shown by the difference in the N-Gain score with the N-Gain score of the experimental class being greater than that of the control class and both including moderate improvement. Meanwhile, in the affective domain, the difference in the average of two meetings between the experimental class and the control class was seen, with the experimental class having a greater increase. So it can be concluded that there is an influence and difference in improving student learning outcomes using the problem based learning model based on puzzle quiz media on the material of the month of Ramadan.